Development of electroless plating processes for low cost plastic-metallization and area-selective metal coating of three-dimensional structures - Zhan, Jing (Nanyang Technological University, 2020)
To spread out the application of electroless plating, several methods were developed to improve the efficiency, cost effectiveness and environmental aspects of the electroless plating process. The author found three exist problems could limit the applications of electroless plating: 1) high market prices and low earth abundance of the catalyst materials (platinum, palladium, etc.); 2) strong or even hazardous acids are used in the surface preparation step; 3) challenged for triggering the electroless deposition on demand. For the initialization of electroless nickel deposition with fewer catalyst nanoparticles (palladium), a pre-treatment process that induces a conductive surface of reduced graphene oxide (rGO) on substrates was added prior to the surface activation step (Pd catalyzation). We confirmed that the rGO treatment enhanced the Pd catalytic activity and achieved a sufficient rate in the electroless deposition with extremely low Pd loading (3.94 x 10-2 g/cm2). In the second project, to avoid environmental contamination and hazards of the whole electroless deposition process, the catalyst palladium was pre-loaded onto Acrylonitrile Butadiene Styrene copolymer (ABS) by an appropriate solvent. The use of Pd-loaded ABS material in additive manufacturing technology eliminated the surface etching steps and maintained sufficient adhesion of metal coating on ABS substrates. In the third project, the author achieved area-selective electroless palladium deposition by separating the reducing agents and metal salts with thermosensitive liposome. With the local thermal treatment above 40 ⁰C, the electroless Pd deposition can be triggered at any exposed or internal surface of the given three-dimensional structures. These three projects had achieved improving the cost-effectiveness of current electroless plating technology, and also extending the applications of electroless plating for localized surface metallization of three-dimensional structures by cooperating with additive manufacturing technology and liposome structures.